The microrelief studies of stainless steel mirrors sputtered with Ar⁺ ions of different energy - Bondarenko, V.N.; Konovalov, V.G.; Solodovchenko, S.I.; Shtan′, A.F.; Ryzhkov, I.V.; Voitsenya, V.S.; Lytvyn, P.M.; Byrka, O.V.; Skorik, O.A. (Вопросы атомной науки и техники, 2018)
Four stainless steel mirror specimens were sputtered to an identical mean thickness of the eroded layer 2 μm with Ar⁺ ions. Each specimen was exposed to ions with one kinetic energy from the followings: 300, 600, 1000, and 1350 eV. With the methods of microscopy and profilometry of microrelief the positive correlation was shown between the r. m. s. roughness, the power spectral density of the Fourier spectrum of the longitudinal wavelengths, on one hand, and the energy of ions, on the other hand.